(untitled) (Damascus University Journal of arts and humanities sciences, 2026)
The research aimed to identify the role of academic flexibility as mediating variable between academic passion and research self-efficacy among a sample of postgraduate students at Damascus University, and to reveal the significance of the differences between the scores of the research sample members’ answers on the academic flexibility scale, the academic passion scale, and the research self-efficacy scale according to the variable: (academic stage). The research adopted the descriptive approach. The researcher applied the academic flexibility scale for students prepared by (Cassidy, 2016), which includes (30) items; the academic passion scale prepared by Peixoto et al. (Peixoto, et al, 2019), which consists of (20) items; and the research self-efficacy scale prepared by the researcher and consists of (50) items. The research sample consisted of (478) male and female students from postgraduate students at Damascus University. Research results: There is a positive statistically significant correlation between the answers of the research sample members on the academic flexibility scale as an mediating variable and between academic passion and research self-efficacy among a sample of postgraduate students at Damascus University. There are statistically significant differences between the average scores of the research sample members on the academic flexibility scale, the academic passion scale, and the research self-efficacy scale attributed to the variable of the academic stage in favor of doctoral students. Research summary: Academic flexibility contributes as mediating variable between academic passion and research self-efficacy among a sample of postgraduate students at Damascus University.